2018
DOI: 10.3389/fphys.2018.01413
|View full text |Cite
|
Sign up to set email alerts
|

Haploid Germ Cells Generated in Organotypic Culture of Testicular Tissue From Prepubertal Boys

Abstract: While in mice various studies have described the completion of spermatogenesis in vitro using either organotypic culture of prepubertal testicular tissue or 3D culture of isolated cells, in humans it has not been possible to achieve germ cell differentiation from immature testicular tissue (ITT). In our study, we evaluated the ability of human ITT to differentiate via a long-term organotypic culture of frozen–thawed 1 mm3 testicular fragments from five prepubertal boys in two different culture media. Tissue an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
70
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 60 publications
9
70
1
Order By: Relevance
“…22 These diploid SCs are able both to self-renew and give rise to differentiated haploid cells at the end of the spermatogenic process. 19 Due to the smallness of testicular biopsies taken for cryopreservation in prepubertal boys, the scarcity of SSCs in the testes, 23 the low efficiency of the transplantation process observed in mice and nonhuman primates, 24,25 and the low proportion of human haploid germ cells generated with IVM, 26 amplification of SSCs is an essential step for fertility restoration.…”
Section: Materials and Methods Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…22 These diploid SCs are able both to self-renew and give rise to differentiated haploid cells at the end of the spermatogenic process. 19 Due to the smallness of testicular biopsies taken for cryopreservation in prepubertal boys, the scarcity of SSCs in the testes, 23 the low efficiency of the transplantation process observed in mice and nonhuman primates, 24,25 and the low proportion of human haploid germ cells generated with IVM, 26 amplification of SSCs is an essential step for fertility restoration.…”
Section: Materials and Methods Methodsmentioning
confidence: 99%
“…50 Culturing unsorted cells prior to cell selection has also been attempted, showing that 50 days in the same culture conditions followed by isolation of ITGα6 + cells resulted in a seven fold enrichment of SSCs. 43 Exclusion of articles in language other than English (26), guidelines (6), reviews (192), scientific video protocols (2), peer comments (5), PhD résumé (1) and erratum (1) Together, these results point to the need to identify the best method to propagate SSCs most efficiently. Recently, Bhang et al discovered that human endothelial TCs secreted GDNF, bFGF, stromal cell-derived factor-1 (SDF-1), macrophage inflammatory protein 2, and insulin-like growth factor-binding protein 2 and could support SSC growth for at least 150 days.…”
Section: Ssc Propagationmentioning
confidence: 99%
See 1 more Smart Citation
“…Frozen-thawed 1-mm 3 testicular fragments collected from prepubertal boys (aged 2-12 years) were cultured in a KSR-based medium supplemented with 5 IU/L of FSH, which after 16 days resulted in the formation of round spermatids. Interestingly, increasing the concentration of FSH from 5 to 50 IU/L failed to induce germ cell differentiation, perhaps due to desensitization of FSH receptors or adenyl cyclase in Sertoli cells [128]. However, it should be noted that currently such in vitro produced haploid male germ cells only serve as a proof-of-principle and would need be further analyzed for their fecundability and epigenetic characteristics before suggesting these techniques for potential clinical trials.…”
Section: Progress Of In Vitro Spermatogenesis In Primatesmentioning
confidence: 99%
“…Hence, explant tissue or organotypic culture that maintains such 3D-organised microenvironment seems to be the most promising approach based on successful differentiation of murine SSCs into functional sperm in vitro [40] and the generation of human haploid germ cells from testicular tissue samples of cancer patients between 2 and 12 years of age [41,42]. However, none of the reported studies demonstrated a system robust enough to differentiate human SSCs into functional sperm so far.…”
Section: Perspectives and Challenges Of Fertility Restoration Strategiesmentioning
confidence: 99%